FACTORS HAVING A NEGATIVE INFLUENCE ON INCREASING THE WELFARE OF THE POPULATION AND REDUCING POVERTY IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2024)
The article analyzes the content and socio-philosophical aspects of problematic issues related to the classification of factors that negatively affect the improvement of the well-being of the population in the conditions of Uzbekistan and their origin. The socio-political aspects of improving the comfortable life of the population in need of social protection, reducing poverty, as well as relevant scientific conclusions and recommendations for solving them are also presented.